Status of Physical Education Learning Assessments of Provincial Administration Organization Schools in the Southern Thailand - Chaicharoen, Naruenat; Tengkusulaiman, Rajasyed; Noopayan, Peerapong (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2019)
The objectives of the research article were to study the status of physical education learning assessments of provincial administration organization schools in the southern Thailand. The instrument used to collect the data are checklist and open ended questionnaires. The population of this study consisted of 58 physical education teacher. The statistics for the data analysis were frequency, percentage, mean and standard deviation. The research found that, most of provincial administration organization physical education teachers in the southern Thailand were bachelor degree graduates and have been teaching 25 hours per week. The standard and indicators of learning of the core curriculum of basic education BE. 2551 were the guidelines of measurement and evaluation in physical education subjects. Most of the teachers as mentioned above, evaluated the knowledge of their students using objective teacher made tests, physical education skills were assessed by both quality and quantity tests, ethics and morals were evaluated by standardized tests, physical fitness was assessed by the health related physical fitness test, and the desired characteristics of the students were evaluated by the standardized interview scores.